2008
DOI: 10.1074/jbc.c800170200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Dependence of Hypoxia-inducible Factors 1α and 2α on mTORC1 and mTORC2

Abstract: Constitutive expression of hypoxia-inducible factor (HIF) has been implicated in several proliferative disorders. Constitutive expression of HIF1␣ and HIF2␣ has been linked to a number of human cancers, especially renal cell carcinoma (RCC), in which HIF2␣ expression is the more important contributor. Expression of HIF1␣ is dependent on the mammalian target of rapamycin (mTOR) and is sensitive to rapamycin. In contrast, there have been no reports linking HIF2␣ expression with mTOR. mTOR exists in two complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
222
1
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(241 citation statements)
references
References 39 publications
(75 reference statements)
8
222
1
10
Order By: Relevance
“…However, effects of PEITC on translation are likely to be complex. For example, we demonstrated that PEITC also decreased expression of HIF2 protein in MCF7 cells [31], although HIF2 RNA does not have a highly structured 5'-UTR and is not effectively repressed by rapamycin [36]. Thus, ITCs may affect global protein production via inhibition of CAP-dependent translation, although some RNAs with highly structured 5'-UTRs might be particularly susceptible.…”
Section: Modulation Of Hypoxia Inducible Factor Activitymentioning
confidence: 95%
See 1 more Smart Citation
“…However, effects of PEITC on translation are likely to be complex. For example, we demonstrated that PEITC also decreased expression of HIF2 protein in MCF7 cells [31], although HIF2 RNA does not have a highly structured 5'-UTR and is not effectively repressed by rapamycin [36]. Thus, ITCs may affect global protein production via inhibition of CAP-dependent translation, although some RNAs with highly structured 5'-UTRs might be particularly susceptible.…”
Section: Modulation Of Hypoxia Inducible Factor Activitymentioning
confidence: 95%
“…This sensitivity is apparent in cells treated with the immunosuppressant rapamycin, an inhibitor of the mammalian target of rapamycin (mTOR)-containing mTORC1 complex, a major regulator of 4E-BP1 phosphorylation. Thus, mTORC1 inhibition leads to 4E-BP1 dephosphorylation and decreased translation of RNAs with highly structured 5'-UTRs, including HIF1 [36]. However, effects of PEITC on translation are likely to be complex.…”
Section: Modulation Of Hypoxia Inducible Factor Activitymentioning
confidence: 99%
“…HIF1a stabilization may be limited to more severe polycystic kidneys than achieved in this model, or cellular signaling changes induced by mutation of the PKD1/ PKD2 genes in autosomal dominant polycystic kidney disease may contribute to HIF1a activation in cysts through constitutive mammalian target of rapamycin activation, [35][36][37] which causes enhanced translation of HIF1a. 38,39 Finally, these studies have developed and validated a noninvasive method of quantification of cystic burden in mice that should prove useful for future studies investigating the genetic basis of, and therapies for, polycystic kidney diseases and renal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…44 Importantly, HIF-1a synthesis is more sensitive to mTOR inhibitors than is HIF-2a. 45 In a study of 160 clear cell RCCs with VHL inactivation, gene expression microarray found 2 subsets of tumors: those that expressed both HIF-1a and HIF-2a (H1H2), and those that expressed only HIF-2a (H2). 43 The H1H2 tumors showed increased Akt/mTOR activation, while H2 tumors showed increased c-Myc expression.…”
Section: Predictors Of Responsementioning
confidence: 99%